Confined Pd clusters with dynamic structure for highly efficient Cascade-type catalysis - Ma, Xiao-Chen; Pu, Chun; Zhang, Yue-Xing; Chang, Gang-Gang; Tian, Ge; Wu, Si-Ming; Liu, Jia-Wen; Hu, Zhi-Yi; Wang, Li-Ying; Yin, Yi-Xia; Janiak, Christoph; Yang, Xiao-Yu (Chemical engineering journal (Lausanne, Switzerland : 1996), 2022)
[Display omitted] •Synthesis of reversible confined Pd clusters by host–guest interaction.•Mechanism of charge transfer and formation of disordered Pd clusters in MOF-253.•Pd@MOF-253 with high catalytic activity for cascade-type catalytic reactions under mild condition.•A unique dynamic structure of active disordered phase of Pd clusters. Efficient regeneration of Pd catalysts is a challenge and has a very high technological importance. Herein, we report confined Pd clusters with the ultrafine size (1.2 nm) and ultralow loading amount (0.14 wt%) in a metal–organic framework (MOF), which could potentially allow for the successive realization of the cascade-type catalytic reaction from starting reagents to final desired products, and thus to avoid the excessive processes, save energy and reduce waste. Experiments and theoretical computations have been conducted to study the strong host–guest interaction between the Pd clusters and the MOF support, leading to the high catalytic activity and dynamic of the Pd clusters. A unique dynamic structure from active disordered arrangement to deactive crystalline arrangement and then back to the active disordered arrangement (>99% of activity after regeneration by simple H2 reduction). The MOF-confined Pd shows excellent catalytic activity (>99% activity), selectivity (around 100%) and stability (>99% activity after recycling) under mild reaction conditions (atmospheric temperature and pressure).